Environmental incentives for and usefulness of textual risk reporting: evidence from Germany - Elshandidy, Tamer; Shrives, Philip J. (Elsevier, 2016)
Drawing on distinct German institutional characteristics related to cultural, legal, financial, and regulatory features, this paper investigates the extent to which environmental incentives influence German non-financial firms in revealing risk information in their annual report narratives. The paper also examines whether risk-related disclosure (aggregate risk reporting and the tone of news about risk) is useful by investigating its impact on market liquidity and investor-perceived risk. We find that the decision to provide or withhold such risk information is less likely to be significantly associated with environmental incentives. Among those incentives, we find that German firms are significantly influenced by their underlying risks rather than other factors including ownership structure, capital structure, external equity finance, and borrowing. The decision to disclose is likely to be influenced by the size of the firm and whether or not it produces lengthy annual reports. The results also suggest that the impact of aggregate risk reporting levels was not observable until a distinction was made between bad and good news about risk. Specifically, we find that the German market tends to positively (negatively) price good (bad) news about risk by either improving (worsening) market liquidity through removing (creating) information asymmetries, or reducing (increasing) investor-perceived risk.